Experiences of infertility among couples in Morocco - Amal Benbella; Amal Benbella; Gitau Mburu; Asmaa Zaidouni; Sanae Elomrani; Abdelhakim Yahyane; Karima Gholbzouri; James Kiarie; Rachid Bezad; Rachid Bezad (Frontiers in Reproductive Health)
IntroductionInfertility has significant implications on health. It affects physical, emotional, and social wellbeing. In Morocco, about 12% of couples or live with infertility. In 2013 the first public Assisted Reproductive Technology (ART) Center was established at the Maternity and Reproductive Health Hospital les Orangers in Rabat, Morocco. This qualitative study explores the experiences of infertility among couples who have benefited from diagnosis and treatment at ART center. The study represents a part of the overall evaluation of this first public ART centre in Morrocco.MethodsData were collected through in-depth patient interviews. A semi-structured interview guide was used to elicit the perspectives and experiences couples with infertility. Data collection occurred between January and March 2023. Inductive thematic analysis was conducted to explore the experiences of infertility among the couples.ResultsThe study showed that couples with infertility were exposed to negative experiences such as (i) biomedical experiences (diagnostic delays, fragmented care, multiplicity of treatments), (ii) social experiences (gendered social pressures, stigma, discrimination, marital challenges, isolation and disrupted social routines), (iii) mental experiences (anger, anxiety, depression, and mood changes) as well as (iv) financial limitations (out of pocket payments and financial indebtedness). Solutions addressing these challenging experiences were suggested by interviewed couples including continued quality and respectful care to enhance biomedical experiences; public education campaigns to educate the public and destigmatize infertility to improve social experience, inclusion of psychosocial services as part of fertility integrated care to enhance psychological experiences, and enhanced financial protection, and service decentralisation to mitigate negative financial pressures.ConclusionCouples with infertility are exposed to various challenges in the biomedical, social, psychological, and financial domains. A health system strengthening approach is essential to address those challenges, and multiple strategies are needed to improve the experiences of couples with infertility in Morocco. Given interconnectedness between biomedical, social, psychological, and financial divers of experiences, a holistic approach is required to comprehensively improve the experiences of infertile couples and address all the issues faced by couples during their treatment journey.